2021
DOI: 10.1021/jacs.1c10045
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Study of Antisolvents on the Stability of Multicomponent Metal Halide Perovskites through Robotics-Based Synthesis and Machine Learning Approaches

Abstract: Antisolvent crystallization methods are frequently used to fabricate high-quality perovskite thin films, to produce sizable single crystals, and to synthesize nanoparticles at room temperature.However, a systematic exploration of the effect of specific antisolvents on the intrinsic stability of multicomponent metal halide perovskites has yet to be demonstrated. Here, we develop a highthroughput experimental workflow that incorporates chemical robotic synthesis, automated characterization, and machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 55 publications
0
59
0
Order By: Relevance
“…[22][23][24] The feasibility and efficiency of high-throughput experiments in the field of lead perovskite photovoltaics were recently demonstrated. [25][26][27][28][29][30] However, the majority of the reported syntheses of double LFPs require high energy input by hydrothermal treatment or calcination. Furthermore, a considerable amount of manual intermediate steps is needed which cannot be automated, as well as the usage of hazardous chemicals such as concentrated HCl in the case of chloride LFPs 1,3,6,7,9,14,17,21 or unstable and aggressive substances for bromide and iodide LFPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] The feasibility and efficiency of high-throughput experiments in the field of lead perovskite photovoltaics were recently demonstrated. [25][26][27][28][29][30] However, the majority of the reported syntheses of double LFPs require high energy input by hydrothermal treatment or calcination. Furthermore, a considerable amount of manual intermediate steps is needed which cannot be automated, as well as the usage of hazardous chemicals such as concentrated HCl in the case of chloride LFPs 1,3,6,7,9,14,17,21 or unstable and aggressive substances for bromide and iodide LFPs.…”
mentioning
confidence: 99%
“…22–24 The feasibility and efficiency of high-throughput experiments in the field of lead perovskite photovoltaics were recently demonstrated. 25–30…”
mentioning
confidence: 99%
“…52−55 In addition, embracing automated robots in the materials lab to perform a series of predesigned experiments can also realize HT synthesis, as illustrated in Figure 1c where 1100 metal halide perovskite thin films with different compositions were fabricated through robotics-based systhesis. 56 HT fabrication is generally followed by HT characterization, as shown in Figure 1d, in which various analysis tools are integrated for on-chip characterization. 57 It is worth noting that one alternative method for HT characterization is increasing the efficiency of a single detector to gain more data.…”
mentioning
confidence: 99%
“…112 It was also demonstrated that with this procedure the calculated critical temperature of decomposition and decomposed phases agree with experimental observation, using the example of high-entropy alloys. 112 The potential large data volume for multicomponent materials is suitable for the application of ML-aided material design, as demonstrated in various multicomponent systems, 56,113 including the high-entropy cases. 114−117 The publication of raw data and ML code with the main results should be encouraged for the study of multicomponent materials using high-throughput methods followed by machine learning techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation